Ethnophysics Study of the Concept of Work and Energy in the Aceh Traditional Game “Taloe Yeye” as Physics Teaching Material - Tri Nurianti; Nur Azizah Lubis; Nurmasyitah Nurmasyitah (Berkala Ilmiah Pendidikan Fisika, 2023)
Local wisdom is a form of human behavior and its relation with the surrounding environment, which is formed naturally and is sourced from customs and ancestral advice. The traditional game of taloe yeye is one of the many traditional games in Indonesia that needs to be preserved. In the taloe yeye game, physics concepts can be integrated into physics learning, one of which is work and energy. The purpose to be achieved from this research is to examine the ethnophysics of the concept of work and energy in the traditional Aceh game taloe yeye, which is expected to be used as physics teaching material. This study uses a qualitative descriptive research method.  Data collection is done by observation and documentation. The data that has been collected is then analyzed using data analysis in stages, namely, reducing the observed data, presenting the data in the form of graphics and descriptive text, and drawing conclusions. The results showed a relationship between taloe yeye players and the concepts of work and energy.  From this concept, students can experience actual learning by studying the physics of work and energy concepts in the taloe yeye game.